Oral health and the risk of head and neck squamous cell carcinoma: a multicenter case-control study in Iran - Hamideh Rashidian; Elham Mohebbi; Maryam Hadji; Mahin Gholipour; Monireh Sadat Seyedsalehi; Ali Akbar Haghdoost; Paolo Boffetta; Sepideh Mokhtari; Kazem Zendehdel (Scientific Reports)
Abstract The current study aimed to assess the independent effect of a high Decayed, Missing, and Filled Teeth (DMFT) score on the risk of head and neck squamous cell carcinoma (HNSCC) overall and its subsites. Also, we tested for the interaction effect of smoking tobacco and opium with the DMFT score on the risk of developing HNSCC. We included 899 pathologically confirmed cases of HNSCC and 3477 healthy visitor controls. We used multivariable unconditional logistic regression analyses to estimate odds ratios (ORs) and 95% confidence intervals (CIs) adjusted for study centers, age, sex, socioeconomic status, and alcohol, cigarettes, water pipes, and opium use. We found an OR of 2.0 (95% CI: 1.6, 2.5) between DMFT scores higher than 17 and the risk of HNSCC. This was higher for laryngeal (OR: 3.6, 95% CI: 2.5, 5.2) than lip oral cavity (OR: 1.5, 95% CI: 1.2, 2.0) cancers. We found a positive association between Decayed and Missing teeth, however, it was reversed for the number of Filled teeth. The association for those who had higher DMFT score was significantly higher (OR: 2.3, 95%CI: 1.7, 3.0) among smokers than non-smokers (OR: 1.7, 95% CI: (1.2, 2.3). A higher DMFT score was associated with an increased risk of HNSCC, with an interaction between DMFT score and smoking.